Публицистика Ивана Ильина - Синица, Д.А. (Культура народов Причерноморья, 2001)
В статье анализируются основные тематические аспекты публицистики И. Ильина. Автор опирается на книгу И. Ильина “Основы христианской культуры”, сборник “Наши задачи”, речи и статьи философа; раскрывает в полемическом плане ильинские представления о христианизации мировой культуры, о национальном и “сверх – национальном”, о задачах литературы, о судьбах “Святой Руси” (термин И.Шмелева) и понятии “окаянная Нерусь”. Внедрение православного духа во все сферы культурного бытия возможно лишь усилиями больших социальных групп, объединений людей, самым устойчивым из которых является нация. There were analysed in the article the main aspects of publicism by I.Ilyin. The writer rests on the book by I.Ilyin "A fundamentals of christian culture", accumulator cell " Our problems ", speeches and the articles of the philosopher; uncovers in the polemic schedule his submissions about christianisation of world culture, about national and " over - national ", about problems of the literature, about fates "Святой Руси " (term by I.Shmelev) and concept " окаянная Нерусь ". Intrusion of orthodox spirit in all orbs of cultural life probably only by efforts of large social groups, affiliations the people, steadiest of which one is the nation.